2021
DOI: 10.1007/s00500-020-05538-8
|View full text |Cite
|
Sign up to set email alerts
|

A multigene genetic programming-based fuzzy regression approach for modelling customer satisfaction based on online reviews

Abstract: In previous studies, customer survey data were commonly adopted to perform the modelling of customer satisfaction (CS). However, it could be time-consuming to conduct surveys and obtain their data. On the other hand, respondents' responses are quite often confined by pre-set questions. Nowadays, a huge number of customer online reviews on products can be found on various websites. The reviews can be extracted easily in a very short time. Customers can freely express their concerns and views of products in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…A dynamic evolving neural-fuzzy inference system was applied for the modeling of variational customer preferences for the design of hair dryers [ 35 ]. Yakubu et al [ 36 ] proposed a multigene genetic programming-based fuzzy regression approach to develop customer preference models based on online reviews. But in addition to the need to address the problem of vagueness, scholars have found that when modeling product design attributes and consumer preferences, the relationships are often highly nonlinear.…”
Section: Related Workmentioning
confidence: 99%
“…A dynamic evolving neural-fuzzy inference system was applied for the modeling of variational customer preferences for the design of hair dryers [ 35 ]. Yakubu et al [ 36 ] proposed a multigene genetic programming-based fuzzy regression approach to develop customer preference models based on online reviews. But in addition to the need to address the problem of vagueness, scholars have found that when modeling product design attributes and consumer preferences, the relationships are often highly nonlinear.…”
Section: Related Workmentioning
confidence: 99%
“…Lawani et al (2018) used the sentiment dictionary to obtain the sentiment scores of reviews as a measure of user satisfaction, and explored the impact of price and distance on user satisfaction. Yakubu et al (2021) used multi-gene genetic programmingbased fuzzy regression (MGGPFR) to obtain the sentiment scores of reviews to analyze the sentiment tendencies of e-commerce users. It is worth noting that the emotional tendencies of a single user can be evaluated by sentiment values.…”
Section: Online Reviews and Machine Learningmentioning
confidence: 99%
“…When analyzing the emotional characteristics of users, researchers often find the emotional tendencies of users by calculating the sentiment value of reviews (Lawani et al, 2018;Yakubu et al, 2021). Some studies use supervised machine learning models such as deep learning to train labeled samples, so as to predict users' emotional tendencies (Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The second step is to classify tweets using multilayer perceptron model. In a recent research work (Yakubu et al 2021 ), customer satisfaction model based on online reviews has been developed, based on the sentiment scores derived by applying a novel multigene genetic programming-based fuzzy regression (MGGP-FR) approach. To address the fuzziness of customer opinions, the sentiment scores are transformed into asymmetrical fuzzy numbers.…”
Section: Related Workmentioning
confidence: 99%